Determination of the reasons for the lower injectivity of the injection wells - Krivova, N. R. (Revista de la Universidad del Zulia, 2020)
The injection of water into the formations to maintain their pressure is accompanied by loss of injectivity in the injection wells. It is necessary to determine the reasons for the loss of injectivity to apply various methods of regulation of the characteristics of the filtration tank in the area of the bottom of the formation, which will allow to restore the injectivity of the wells and increase the coverage of the formation by flooding. of water. The document presents the results of the determination of the alleged causes of a loss of injection well injection, the hypotheses to determine the causes of a loss of injection and the studies conducted to confirm or refute the causes mentioned.